INFORMATION TECHNOLOGY OF MANAGEMENT OF LEARNING LOAD IN INSTITUTIONS OF HIGHER EDUCATION - V.G. Gritsenko (Kherson State University, 2010)
The article deals with the problems of the ICT development and application of the learning load management in institutions of higher education.